2009
DOI: 10.1542/peds.2008-0763
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Rates for Extremely Low Birth Weight Infants Born in Japan in 2005

Abstract: The mortality rates of extremely low birth weight infants who were born in 2005 demonstrated definite improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
185
6
17

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(220 citation statements)
references
References 14 publications
10
185
6
17
Order By: Relevance
“…5,7,10,11,14,[16][17][18]20,36,37,47 Other studies include only infants admitted to the NICU, with survival rates ranging from 0% to 66%. 4,9,[11][12][13][14][15]17,18,20,21,23,24,34 Previous Canadian studies that did not include stillbirth noted survival rates in infants admitted to the NICU of 35.2% to 41.7%. 4,15,24 The survival rate was lower in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,7,10,11,14,[16][17][18]20,36,37,47 Other studies include only infants admitted to the NICU, with survival rates ranging from 0% to 66%. 4,9,[11][12][13][14][15]17,18,20,21,23,24,34 Previous Canadian studies that did not include stillbirth noted survival rates in infants admitted to the NICU of 35.2% to 41.7%. 4,15,24 The survival rate was lower in our study.…”
Section: Discussionmentioning
confidence: 99%
“…29,[40][41][42][43][44] Finally, a number of studies present data from populations that may differ from the Canadian population with respect to ethnicity and access to health care. 3,[7][8][9][10][11][12][13][14][16][17][18][19][20][21][22][23]34,45 Few studies have evaluated maternal outcomes of women delivering at a periviable gestation.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Japan has recently reported intact survival rates for infants born alive at 22 weeks of gestation comparable to those born at 23 weeks of gestation, with overall survival rates of 33%. 28 A study in the United States found similar rates of survival among newborn infants born at 22 weeks' gestation. 29 Therefore, if survival were the only consideration, it would seem reasonable to offer resuscitation and intensive care to all infants born at or beyond 22 weeks of gestation.…”
Section: Outcome According To Gestational Agementioning
confidence: 98%
“…With the increased survival of extremely preterm infants (<28 weeks of gestation), 1 uncertainty about their neurodevelopmental (ND) outcome has become of paramount concern. Along with intraventricular hemorrhage (IVH), cerebellar hemorrhage (CH) may represent a major risk factor for ND problems in these preterm infants.…”
Section: Introductionmentioning
confidence: 99%